2023
DOI: 10.1093/procel/pwad021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the microbiome on mosquito-borne diseases

Abstract: Mosquito-borne diseases present a significant threat to human health, with the possibility of outbreaks of new mosquito-borne diseases always looming. Unfortunately, current measures to combat these diseases such as vaccines and drugs are often either unavailable or ineffective. However, recent studies on microbiomes may reveal promising strategies to fight these diseases. In this review, we examine recent advances in our understanding of the effects of both the mosquito and vertebrate microbiomes on mosquito-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 267 publications
0
6
0
Order By: Relevance
“…Gut-resident microbes regulate mosquito defense against viral invasion into the intestinal epithelium by modulating physiological and immune homeostasis ( 47 ). In this study, we isolated a Rosenbergiella bacterium from the gut of field A. albopictus mosquitoes that rendered mosquitoes significantly less susceptible to flavivirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Gut-resident microbes regulate mosquito defense against viral invasion into the intestinal epithelium by modulating physiological and immune homeostasis ( 47 ). In this study, we isolated a Rosenbergiella bacterium from the gut of field A. albopictus mosquitoes that rendered mosquitoes significantly less susceptible to flavivirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of viromes across various arthropods, including ticks, mosquitoes, sandflies, etc., using high-throughput sequencing has led to the discovery of a large number of viruses, most of which can be classified as insect-specific viruses [ 1 , 4 , 73 , 74 , 75 ]. These viruses belong to different families and orders [ 73 , 76 ], naturally infect arthropods, and replicate in arthropods and/or insect cell lines, but their distinctive feature is their inability to replicate in vertebrates and their cells [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…During hematophagy, arthropods acquire various factors, including components from host blood and metabolites from commensal microbes, which might influence viral transmission [ 114 , 115 , 116 , 117 , 118 ]. A recent finding revealed that mosquitoes acquire a host-derived miRNA, known as miR-150-5p, which has been shown to downregulate the expression of the thrombospondin-related anonymous protein AaCT-1 mRNA, thereby disrupting the RNAi antiviral framework and promoting DENV infection and propagation in the mosquito [ 36 ].…”
Section: The Roles Of Noncoding Rnas In Vector-mediated Flavivirus In...mentioning
confidence: 99%